2021
DOI: 10.3390/membranes11030181
|View full text |Cite
|
Sign up to set email alerts
|

Nonwoven Ion-Exchange Membranes with High Protein Binding Capacity for Bioseparations

Abstract: This study presents the preparation and characterization of UV-grafted polybutylene terepthalate (PBT) ion exchange nonwoven membranes for chromatographic purification of biomolecules. The PBT nonwoven was functionalized with sulfonate and secondary amine for cation and anion exchange (CEX and AEX), respectively. The anion exchange membrane showed an equilibrium static binding capacity of 1300 mg BSA/g of membrane, while the cationic membranes achieved a maximum equilibrium binding capacity of over 700 mg hIgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Due to the higher binding capacity obtained by linking IDA onto the membranes at pH 10.0, we employed this reaction condition for the studies that followed. Prior work in our lab [ 34 , 42 ] indicated that ion-exchange membranes prepared by grafting polyGMA at 20% WG showed higher protein-binding capacity while maintaining excellent flow permeability. As a result, all CEX-IDA membranes used in the following studies were prepared based on 20% WG polyGMA grafted membranes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the higher binding capacity obtained by linking IDA onto the membranes at pH 10.0, we employed this reaction condition for the studies that followed. Prior work in our lab [ 34 , 42 ] indicated that ion-exchange membranes prepared by grafting polyGMA at 20% WG showed higher protein-binding capacity while maintaining excellent flow permeability. As a result, all CEX-IDA membranes used in the following studies were prepared based on 20% WG polyGMA grafted membranes.…”
Section: Resultsmentioning
confidence: 99%
“… 1 For the two membrane types, the experiments were performed using the same conditions with 12 membrane layers packed in a 12 cm diameter column. All details of CEX-SO 3 membrane experiments are reported in [ 34 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It can be processed by several available techniques and is readily dissolvable in methylene chloride. This creates a possible route for electrospinning into microporous non-woven structures [ 23 , 24 ]. The porous polymer composites are very important and have been widely used in many practical applications, such as fibrous porous media [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane ion-exchange chromatography promises several advantages over column chromatography, including low operating pressure and fast flow rates, ease of use, and elimination of cleaning and validation costs in single-use applications. To this end, Lemma et al [4] developed and characterized ion-exchange nonwoven membranes for the chromatographic purification of biomolecules. UV-grafted polybutylene terepthalate were prepared and functionalized with sulfonate and secondary amine for cation and anion exchange, respectively.…”
mentioning
confidence: 99%